PENDIDIKAN MULTIKULTURAL DI INDONESIA SEBAGAI UPAYA MENINGKATKAN TOLERANSI DAN PEMAHAMAN ANTAR BUDAYA - Toat Haryanto; Saepudin Zuhri (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2025)
This research is motivated by the need to understand the role of multicultural education in improving tolerance and understanding among cultures in Indonesia, known for its diversity. Although it has been implemented in national education policies, the implementation of multicultural education on the ground still faces various challenges, such as limited resources and lack of teacher training. The purpose of this research is to identify the factors affecting the effectiveness of multicultural education and uncover how it can be more optimally applied in Indonesian schools. The methodology used in this research is a qualitative approach with a case study design, where data were collected through in-depth interviews, observations, and documentary studies related to multicultural education. The research findings show that, while multicultural education has great potential to improve tolerance and cultural understanding, its implementation is still limited and not optimal in many schools. Several factors influencing this implementation include insufficient teacher training, lack of adequate resources, and policies that are not fully supportive. This research contributes significantly to the development of policies and strategies to improve the quality of multicultural education in Indonesia, by considering local needs and providing sufficient training for teachers